Diversity in the teaching of Tilawah al-Quran in Malaysian secondary schools - Che Noh, Mohd Aderi; Suhid, Asmawati; Yamat, Hamidah (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
The teaching of Tilawah al-Quran or Quranic Recitation is an important component for the subject of Islamic Education in the Secondary School Integrated Curriculum (KBSM). The purpose of teaching Quranic Recitation is to educate students from various quranic background knowledge to be able to recite, memorize, comprehend and practice the teachings of the Quran. This paper presents the findings of a study in regards to students' perceptions on the teaching of Quranic Recitation in the school integrated curriculum. A total of 1651 Form Two students from various quranic background knowledge are involved in this study. Students responded to a five-point likert scale questionnaire which consists of 69 indicators related to the topics in this study. The findings are presented in descriptive statistics of frequency, percentage and mean. The data show that students from various quranic background knowledge generally perceived their teachers' teaching of the Quranic Recitation is at a moderate level.